2013
DOI: 10.1186/1471-2164-14-862
|View full text |Cite
|
Sign up to set email alerts
|

De novo characterization of the gene-rich transcriptomes of two color-polymorphic spiders, Theridion grallator and T. californicum (Araneae: Theridiidae), with special reference to pigment genes

Abstract: BackgroundA number of spider species within the family Theridiidae exhibit a dramatic abdominal (opisthosomal) color polymorphism. The polymorphism is inherited in a broadly Mendelian fashion and in some species consists of dozens of discrete morphs that are convergent across taxa and populations. Few genomic resources exist for spiders. Here, as a first necessary step towards identifying the genetic basis for this trait we present the near complete transcriptomes of two species: the Hawaiian happy-face spider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 91 publications
7
48
0
Order By: Relevance
“…Although ommochrome pigments are absent in white Bombyx wings, they are present in wings of Nympalidae butterflies such as Heliconius species and Precis coenia (Butenandt and Schafer, 1962;Gilbert et al, 1988;Nijhout, 1997), and phenoxazinone synthetase activity has been detected in pupal P. coenia wings (Nijhout, 1997). We confirmed the presence of cardinal gene homolog in the developing wing expressed sequence tag data set of Heliconius erato (IC33431AfEcon6544) (Hines et al, 2012) by tBlastn search (http://butterflygenome.org/), and the cardinal gene homolog was also reported in the transcriptomes of Hawaiian happy-face spiders (Croucher et al, 2013). It may be of interest to determine whether the cardinal gene ortholog is involved in coloration of butterfly wings and spider bodies.…”
Section: Discussionsupporting
confidence: 59%
“…Although ommochrome pigments are absent in white Bombyx wings, they are present in wings of Nympalidae butterflies such as Heliconius species and Precis coenia (Butenandt and Schafer, 1962;Gilbert et al, 1988;Nijhout, 1997), and phenoxazinone synthetase activity has been detected in pupal P. coenia wings (Nijhout, 1997). We confirmed the presence of cardinal gene homolog in the developing wing expressed sequence tag data set of Heliconius erato (IC33431AfEcon6544) (Hines et al, 2012) by tBlastn search (http://butterflygenome.org/), and the cardinal gene homolog was also reported in the transcriptomes of Hawaiian happy-face spiders (Croucher et al, 2013). It may be of interest to determine whether the cardinal gene ortholog is involved in coloration of butterfly wings and spider bodies.…”
Section: Discussionsupporting
confidence: 59%
“…That the biosynthetic pathway of melanin in spiders was not detected in a recent genomic study may simply illustrate a limitation of homologous sequence comparison to identify evolutionary shifts in enzymes. Genes associated with melanin pigmentation that were not found in spiders include: ebony, eiger, grim, Gustatory receptor 28b, Melanization protein 1, Peptidoglycan recognition protein LC, Serine protease 7, Serpin 27A, Serpin 77Ba, yellow, yellow-f and yellow-f2 (Croucher et al, 2013). However, seven genes associated with melanin synthesis were found in the same study (Croucher et al, 2013): basket, dorsal, hemipterous, Hemolectin, Neuroglian, Rho1 and Toll.…”
Section: Discussionmentioning
confidence: 74%
“…Genes associated with melanin pigmentation that were not found in spiders include: ebony, eiger, grim, Gustatory receptor 28b, Melanization protein 1, Peptidoglycan recognition protein LC, Serine protease 7, Serpin 27A, Serpin 77Ba, yellow, yellow-f and yellow-f2 (Croucher et al, 2013). However, seven genes associated with melanin synthesis were found in the same study (Croucher et al, 2013): basket, dorsal, hemipterous, Hemolectin, Neuroglian, Rho1 and Toll. Spiders may use different enzymes or substrates to synthesize melanins, as is true in insects that produce pheomelanin (Galván et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…S1) than 3OH-kynurenine and cannot be detected by Raman, but have been successfully detected by SERS (Smyth et al, 2011). Pterins are abundant in insects (Shamim et al, 2014), and a previous genomic study suggested that pterins could be synthesized de novo in spiders (Croucher et al, 2013). Therefore, pterins could also be responsible for the colour production of these yellow setae.…”
Section: Discussionmentioning
confidence: 99%